Diseminasi Informasi dan Promosi melalui Instagram @kebunraya_id - Sufa, Fadhila Faella; Priatna, Wahyu Budi (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The rapid development of social media has transformed how institutions disseminate information and conduct promotional activities to the public. Instagram has become a widely used platform for delivering information in a fast, visual, and interactive manner, enabling institutions to reach broader audiences while strengthening their institutional image in the digital environment. In this context, this study examines the practice of information dissemination and promotion through the official Instagram account @kebunraya_id. This study employs a qualitative approach with a descriptive method. Data were collected through observation of Instagram content posted on @kebunraya_id from September to December 2025, unstructured interviews Digital Strategist and Social Media Admin of Kebun Raya, and documentation of posts related to informational and promotional activities. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that Instagram functions as an effective medium for disseminating information and promoting Kebun Raya as an educational and recreational tourism destination. Information dissemination is carried out through educational and greetings content, while promotional activities are presented through recreation and tourism content. The communication strategy integrates educational values, appealing visual elements, and interactive engagement with audiences, although several challenges remain, including time management, inter-division coordination, and the content approval process.